The E2F-1 associated retinoblastoma-susceptibility gene product is modified by O-GlcNAc - Wells, Lance (2010)
The retinoblastoma-susceptibility gene product (pRB) is a classical tumor suppressor. pRB regulates a number of cellular processes including proliferation, differentiation, and apoptosis. One of the essential mechanisms by which pRB, and the related p107 and p130 family members, act is through its interactions with the E2F class of transcription factors. E2F-1 transcription is necessary for entry into S-phase during the cell-cycle. pRB binds E2F-1 and represses transcription via recruitment of a histone deacetylase complex and by preventing co-activator complexes from binding E2F-1. Current dogma suggests that phosphorylation of pRB during mid- to late-G1 leads to release of E2F-1 and E2F-1 dependent transcriptional activation of essential S-phase genes. Here we show that pRB, and the related p107 protein, are modified by O-linked β-N-acetylglucosamine (O-GlcNAc) in an in vitro transcription/translation system. Furthermore, we show in vivo that pRB is more heavily glycosylated in G1 of the cell-cycle when pRB is known to be in an active, hypophosphorylated state. Finally, we demonstrate that E2F-1 associated pRB is modified by O-GlcNAc. These studies suggest that regulation of pRB function(s) may be controlled by dynamic O-GlcNAc modification, as well as phosphorylation.